DEVELOPMENT OF KINTARI LEARNING MEDIA FOR 5TH GRADE STUDENTS OF SDN 4 ANGGREK, NORTH GORONTALO DISTRICT - Mokoagow, Nurchalis; Pulukadang, Wiwy Triyanty; Hendrayanto, Hendrayanto (JPSD (Jurnal Pendidikan Sekolah Dasar), 2025)
This research aims to develop the Kintari learning media to motivate the learning of 5th-grade students at SDN 4 Anggrek, North Gorontalo Regency, and to measure the level of suitability of the Kintari learning media for 5th-grade students at SDN 4 Anggrek, North Gorontalo Regency. This research uses the Research and Development method using the ADDIE model (Analyze, Design, Development, Implementation, and Evaluation). This research was conducted at SDN 4 Anggrek, North Gorontalo Regency. Data collection techniques used were interviews, observation, questionnaires, and documentation. This research produced a Kintari learning media product for 5th-grade students at SDN 4 Anggrek, North Gorontalo Regency. The feasibility test carried out by experts resulted in an average score of 91.9% in the “Very Feasible“ category. Thus, the Kintari learning media product for 5th-grade students at SDN 4 Anggrek, North Gorontalo Regency, which researchers developed, is suitable for implementation.